BRAND BUILDING WITH SOCIAL MEDIA IN B2B BORN GLOBAL COMPANIES - Rahunen, Noora (My University, 2019)
The aim of this master's thesis is to uncover the ways how born global companies, operating in the B2B sector, can implement successful brand building in social media when expanding to a new international market, since rapid internationalization is an important characteristic for the born global companies. The link between utilizing social media in brand building and the internationalization of born globals is a relevant topic for this research, because even though one of the most important marketing themes in the research world has been a brand and its benefits for a company, too little effort has been invested in the brand building actions in the B2B field. In addition, the utilization of social media in branding with deliverable results has remained to be problematic among many B2B companies. This research includes a qualitative case study with two B2B born global companies; Leadfeeder and Vainu.io, who both have successfully entered several international markets early after their founding. In this study, the used data collection method is semi-structured interviews and the analysis of the empirical material has been carried out using a theory- based content analysis. Based on the theoretical framework and the empirical results, the role of social media in B2B brand building is found to be diverse but decisive, since it can effectively support the internationalization of born globals. The results in this study are not intended to be generalized, but to be used as guidelines when building a brand with social media in the B2B field, taking into account the characteristics of the born global companies.
Keywords: born global; internationalization; B2B; brand building; social media; fi=Johtaminen ja organisaatiot|en=Management and Organization|; Master’s Programme in Strategic Business Development